Análise multilocus de parâmetros populacionais, evolução molecular e diferenciação em espécies de moscas-das-frutas do grupo fraterculus (Diptera, Tephritidae) - Fernandes, Fernanda (2010)
The genus Anastrepha which is endemic to the Neotropical region has big economic importance to cause great losses in fruit production. We studied three species of the cryptic group fraterculus: Anastrepha fraterculus, A. obliqua and A. sororcula. Although no single marker is able to distinguish these species, some morphological and behavioral markers are able to distinguish them. There is evidence that these markers do not match the patterns of genetic variation and divergence of these flies. We investigated the role of genes related or not to reproduction in the speciation of these flies. We used a cDNA library of the reproductive tissues of females of A. fraterculus, to isolate expressed genes from those tissues. From a framework of divergence population genetics, we estimated relevant demographic parameters that reported the genetic architecture of speciation in this group. To study the separation of these species, we used gene trees as a framework to be compared and to infer eventual species trees. We amplified 12 genes isolated from the cDNA library. The analysis of population divergence and levels of polymorphism were made in DNAsp and showed high levels of polymorphism for the vast majority of loci. Neutrality tests reveal that only Fs Fu was significantly negative for the combination of species here considered. These results indicate a possible evidence of population expansion on this group of species. These data were corroborated by the values of ancestral and current theta estimated from the analysis undertaken on the software IMa2 program. These analysis also showed relevant levels of migration in some contrasts, but particularly among species which are more distant in the tree from the other two. However, the same analyses performed amongst species pairs fail to reveal high levels of migration rate among species, though t e theta values were close to those estimated in the analysis with all three species together. We also tested for the presence of selection at different loci, using the program PAML and obtained evidence of positive selection for three genes CG7203, CG8064 and MLC, whereas the gene CG7009 showed evolution by a mild purifying selection. The haplotype networks showed the grouping of haplotypes of the species for five of the 12 genes CG7009, CG8064, Elp, TCTP and Cyclophylin. CG7009 revealed possible species specific markers for A. sororcula. We carried out the deep coalescence analysis in the program MESQUITE, comparing gene trees simulated with real trees for each gene locus, placing the species as an outgroup for each tree model and obtained significant results, which would be compatible to simulated scenarios only for the genes V Cyclophylin and TCTP. The tree obtained by minimizing the deep coalescence estimated showed that A. sororcula is farther from the other two species of the genus Anastrepha. It is necessary, however, a larger investigation of different genes, particularly genes with higher evolutionary rates and an expansion of the samples of these species to consider geographical distribution and assist in studies of speciation of this group.